Functional characteristics of the brain in college students with internet gaming disorder. - Liu, Jun; Li, Weihui; Zhou, Shunke; Zhang, Li; Wang, Zhiyuan; Zhang, Yan; Jiang, Yebin; Li, Lingjiang (Brain Imaging & Behavior, 2016)
Internet gaming disorder (IGD) is a subtype of internet addiction disorder (IAD), but its pathogenesis remains unclear. This study investigated brain function in IGD individuals using task-state functional magnetic resonance imaging (fMRI). It is a prospective study in 19 IGD individuals and 19 matched healthy controls. They all received internet videogame stimuli while a 3.0 T fMRI was used to assess echo planar imaging. Brain activity was analyzed using the Brain Voyager software package. Functional data were spatially smoothed using Gaussian kernel. The threshold level was positioned at 10 pixels, and the activation range threshold was set to 10 voxels. Activated brain regions were compared between the two groups, as well as the amount of activated voxels. The internet videogame stimuli activated brain regions in both groups. Compared with controls, the IGD group showed increased activation in the right superior parietal lobule, right insular lobe, right precuneus, right cingulated gyrus, right superior temporal gyrus, and left brainstem. There was a significant difference in the number of activated voxels between the two groups. An average of 1078 voxels was activated in the IGD group compared with only 232 in the control group. Internet videogame play activates the vision, space, attention, and execution centers located in the occipital, temporal, parietal, and frontal gyri. Abnormal brain function was noted in IGD subjects, with hypofunction of the frontal cortex. IGD subjects showed laterality activation of the right cerebral hemisphere.